2016
DOI: 10.14485/hbpr.3.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of School Recess to Daily Physical Activity: Systematic Review and Evidence Appraisal

Abstract: The present study aimed to estimate school recess moderate-vigorous intensity physical activity (MVPA). Methods: A systematic review was carried out in MEDLINE and SportDiscus to identify observational studies where MVPA had been measured objectively during school recess. Study quality was assessed formally. Results: Twenty-four eligible studies in primary school pupils (N= 5,778 individuals), revealed a weighted mean of 12 minutes MVPA per school day. Only two eligible studies were identified in high school p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 13 publications
3
26
0
Order By: Relevance
“…Another opportunity for children and adolescents to be physically active is during recess and PEC . However, our results indicated that children and adolescents only spend around 5–10 minutes in MVPA during recess and PEC, which is in line with that was found in previous studies . Only 10% of child boys spent half of recess time in MVPA, which is consistent with percentages reported by Stratton and Mullan .…”
Section: Discussionsupporting
confidence: 92%
“…Another opportunity for children and adolescents to be physically active is during recess and PEC . However, our results indicated that children and adolescents only spend around 5–10 minutes in MVPA during recess and PEC, which is in line with that was found in previous studies . Only 10% of child boys spent half of recess time in MVPA, which is consistent with percentages reported by Stratton and Mullan .…”
Section: Discussionsupporting
confidence: 92%
“…This recommendation, in fact, sets a goal in an absolute value (minutes of MVPA), and school hours are not the same in all countries [9][10][11][12] Traditionally, school leisure time (i.e., time periods of noncurricular activities in school, such as recess, breaks or lunchtime) and physical education lessons have been considered the most propitious periods to help students meet the aforementioned school-based PA recommendations [13][14][15]. For this reason, levels of PA during both periods have received considerable attention and have been the subject of prior systematic reviews [16,17]. However, in most countries, recess time is limited (approximately 30 min per day), and physical education is given relatively little time in the curriculum (approximately 2 h per week) [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, in most countries, recess time is limited (approximately 30 min per day), and physical education is given relatively little time in the curriculum (approximately 2 h per week) [18]. Moreover, recent studies have shown that less than half of recess time and physical education lessons are spent in MVPA [9,16,17] and that there are more ways to accumulate MVPA during school hours (e.g., breaks, lunchtime or during academic lessons) that have been undervalued to date [19].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In addition, recent systematic reviews suggest that the school-based domains (PE, recess, active commuting to school) which have been the focus of most previous research and policy effort may contribute relatively little to population MVPA at present. [23][24][25] Comparisons of the likely effect of different interventions on population MVPA 20,26 also suggest that future efforts should extend beyond the school.…”
Section: Key Health Behaviors and Outcomes Related To Physical Activimentioning
confidence: 99%